ILRI and BecA support Australia's Engagement with Africa - International Livestock Research Institute (International Livestock Research Institute, 2009)
Percy Stanley, AusAID’s Counsellor Development Co-operation for Africa, talks about Australia’s interest to engage with Africa and identifies the International Livestock Research Institute (ILRI) and Biosciences Eastern and Central Africa (BecA) as good bridges for achieving this. This was during a visit to ILRI and BecA in Nairobi, Kenya (East Africa) on November 3 2009. The AusAID counsellor also mentions the opportunities that this engagement presents both Australia and Africa including collaboration between scientists from both continents.